Report on the Geomagnetic Electrokinetograph (2nd). The General Theory of the Electric Potential Field Induced in Deep Ocean Currents - Stommel, Henry; von Arx, William S. (1948)
The Geomagnetic Electrokinetograph is an instrument of great simplicity which is capable of measuring the motions of sea water from a moving vessel. The motions of the sea may result from any cause, wind drift, waves, currents, and their eddies, tides, seiches, tsunamis or artifacts and still be suitable objects of study. The basic performance of the instrument depends upon Faraday's Law of Electromagnetic Induction, particularly the special case which he mentioned in his Bakerian Lecture to the Royal Society in 1832: 'Theoretically, it seems a necessary consequence that where water is flowing, there electric currents should be formed: thus, if a line be imagined passing from Dover to Calais through the sea, and returning through the land beneath the water to Dover, it traces out a circuit of conducting matter, one part of which, when the water moves up or down the channel, is cutting the magnetic curves of the earth, whilst the other is relatively at rest . Where the lateral extent of the moving water is enormously increased, it does not seem improbable that the effect should become sensible; and the Gulf Stream may thus, perhaps, from electric currents moving across it, by magneto-electric induction from the earth. This is a clear statement of the effect which has subsequently been observed, but which Faraday himself failed to detect through a lack of suitable electrode materials. Includes first report dated Jun 47.